EFFECT OF PBL INTEGRATED WITH STEM ON STUDENTS' SYSTEMS THINKING IN ALTERNATIVE ENERGY - Yani Permata Sakti, Yuli; Anggreini, Anggreini; Distrik, I Wayan; Viyanti, Viyanti (EduFisika: Jurnal Pendidikan Fisika, 2026)
Systems thinking is one of the essential abilities needed to address global challenges in the 21st century because it enables students to understand the relationships among components and the dynamics within a system comprehensively. However, preliminary study results showed that students’ systems thinking ability had not been measured in physics learning, particularly on the topic of alternative energy. Therefore, the implementation of the Problem Based Learning (PBL) model with a STEM approach is expected to support the development of students’ systems thinking ability. This study aimed to determine the effect of the PBL model with a STEM approach on students’ systems thinking ability regarding the topic of alternative energy. The study employed a quasi-experimental method using a non-equivalent control group pretest-posttest design. The sample was selected through purposive sampling, involving class X1 as the experimental class and class X3 as the control class at SMAN 1 OKU. Data were collected using pretest and posttest instruments consisting of 12 two-tier multiple-choice questions. The results showed that the experimental class achieved a higher average n-gain score (0.42, moderate category) compared to the control class (0.29, low category). Furthermore, the independent samples t-test result showed a significance value of 0.004 < 0.05, with an effect size value of 0.337 in the large category. These findings indicate that the implementation of the PBL model with a STEM approach significantly affects students’ systems thinking ability on the topic of alternative energy.